2021
DOI: 10.52567/pjsr.v2i02.7
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Educational Policies of Pakistan

Abstract: Education is the backbone for the development of any country in the world. It lays the foundation for social, political and economic uplift. It is widely accepted that for the prosperity of any country, quality education of their citizens is indispensable. Quality education is only possible if there are good governmental policies for its implementation. Pakistan is among the underdeveloped nations of the world and faced critical problems of education over the past many years. After the independence, from 1947 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Research studies have also identified that the government of Pakistan has formulated new education policies regularly but ignored the factors and reasons that contributed to the failure of previous policies (Ahsan, 2003;Hussain, 2015;Nabi & Nazir, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have also identified that the government of Pakistan has formulated new education policies regularly but ignored the factors and reasons that contributed to the failure of previous policies (Ahsan, 2003;Hussain, 2015;Nabi & Nazir, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study adds the most important factor which is gender disparity to the non‐attainment of universal primary education in Pakistan. Research studies have also identified that the government of Pakistan has formulated new education policies regularly but ignored the factors and reasons that contributed to the failure of previous policies (Ahsan, 2003; Hussain, 2015; Nabi & Nazir, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is substantial to explore all the elements of the education that foretell and sustain the academic success of the students to make them more successful and enduring learners who will make effective inspirations to society. Education is the greatest source of development and progress in all walks of life (Nabi & Nazir, 2020).…”
Section: Introductionmentioning
confidence: 99%